2019 Social Accounting Matrix for Papua New Guinea (PNG) - Pradesha, Angga; Dorosh, Paul A. (International Food Policy Research Institute, 2022)
The Nexus Project is a collaboration between IFPRI and its partners, including national statistical agencies and research institutions. Our aim is to improve the quality of social accounting matrices (SAMs) used for computable general equilibrium (CGE) modeling. The Nexus Project develops toolkits and establishes common data standards, procedures, and classification systems for constructing and updating national SAMs. This addresses the need for greater transparency and consistency in SAM construction to strengthen model-based research and policy analysis in developing countries. Nexus SAMs allow for more robust cross-country comparisons of national economic structure, especially agriculture-food systems. The Nexus Project’s guiding principles are that all data should be traceable to original sources and/or assumptions, and that all SAMs should be freely available online. Greater transparency and accessibility should facilitate more data validation and participation of the modeling community. Statistics are continuously being revised and errors are often only identified when data is used for analysis, and so we welcome your suggestions on how the SAMs can be improved to reflect new and/or better information.